Effects of Soy Isoflavones on Glycemic Parameters and Blood Pressure in Peritoneal Dialysis Patients: A Randomized, Double Blind, Placebo-Controlled Trial (Iranian Journal of Kidney Diseases, 2021)
Introduction. High serum concentrations of glucose, advanced glycation end products (AGEs), and hypertension are some of the major risk factors for cardiovascular disease and peritoneal membrane fibrosis in peritoneal dialysis (PD) patients. Some investigations in nonuremic individuals have indicated that isoflavones can reduce serum glucose, blood pressure, and increase insulin sensitivity. However, such study in this field in PD patients is still lacking. Therefore, we aimed to determine the effects of isoflavones on serum glucose, fructosamine, AGEs, and blood pressure in PD patients. Methods. This study was a randomized, double blind, placebocontrolled trial. Thirty-eight PD patients were randomly assigned to either the isoflavone group or the placebo. The patients in the isoflavone group received 100 mg/d soy isoflavone for 8 weeks, while the control group received corresponding placebo. At baseline and the end of the 8th week, 7 mL of blood was collected from each patient and serum glucose, fructosamine, carboxymethyl lysine, pentosidine, accompanied by systolic and diastolic blood pressures were measured. Results. Serum glucose and pentosidine reduced significantly in the isoflavone group at the end of 8th week compared with baseline (P < .05), whereas no statistically significant changes were observed in the placebo group. Serum carboxymethyl lysine, fructosamine, and systolic and diastolic blood pressures did not significantly change within each group during the study. Conclusion. This study indicates that soy isoflavones could decrease serum glucose and pentosidine in PD patients.